INFLUENCE OF FINANCIAL INCLUSION ON PERFORMANCE OF MICRO AND SMALL ENTERPRISES IN KERICHO COUNTY, KENYA - SANG’, MATILDA CHEMUTAI (KABARAK UNIVERSITY, 2021)
Financing has been identified as a key element for micro and small enterprises to thrive in their drive to build productive capacity, to compete, create jobs and to contribute to poverty alleviation in developing countries. Financial Inclusion consists of all initiatives to make financing a realization for this group. Researchers have argued that lack of financing is almost universally indicated as a key problem for micro and small enterprises thus the need to study influence of financial inclusion on performance of these enterprises. The purpose of the study was to find out the influence of financial inclusion on performance of micro and small enterprises in Kericho County, Kenya. The study was guided by the following specific objectives: to establish the influence of financial access on performance of micro and small enterprises, to determine the influence of financial transparency on performance of micro and small enterprises, to examine the influence of financial credit product on performance of micro and small enterprises and to assess financial literacy of micro and small entrepreneurs and how it influences performance. The study adopted a cross sectional survey design from a population of 7277 micro and small enterprises in Kericho County. Stratified and simple random sampling was used to sample the 380 micro and small enterprises. Questionnaires were used in the data collection phase of the study. Cronbach‟s alpha was used to assess the degree of instrument reliability while factor analysis was used to check validity of the variables. The data was analysed using both descriptive and inferential statistics. Descriptive statistics included frequencies and percentages while inferential statistics included correlation and regression analysis models with the aid of SPSS version 25. The research findings indicated that there exists a statistically significant positive causal relationship between financial access, financial transparency, financial credit products and financial literacy and performance among micro and small enterprises to credit in Kericho County. This was established from correlation results between the two variables. Results showed a statistically significant positive relationship between financial access and performance (r = 0.215, p < 0.05), financial transparency and performance (r = 0.251, p < 0.05), financial credit products and performance (r = 0.222, p < 0.05) and financial literacy and performance (r = 0.293, p < 0.05). This implies that when financial access, financial transparency, financial literacy and financial credit products increases, performance improves among micro and small enterprises in Kericho County, Kenya. Further, interest rates capping significantly moderates the influence of financial access, financial transparency, financial credit products, and financial literacy on performance of micro and small enterprises in Kericho, Kenya. It was concluded that repayment period for MSEs loan was not flexible even after top up or second facility. Micro and small enterprises need guarantors to access financial credit facilities and that they need guarantors to access financial credit facilities for a second or top up facility. Further, collateral and guarantors were needed before credit was given to micro and small enterprises, with financial institutions not having flexible repayment period for loans. Financial institutions did not embrace financial literacy of the micro and small enterprises. The study also concluded that the micro and small enterprises were not provided forums to be educated and informed on any new and changing financial information. The study recommended that financial institutions come up with new products to cover micro and small enterprises financial needs. Further, the study recommended policy formulation and amendments that will include transparency of financial institutions to upheld inclusion of financing. Fora and workshops to be created to educate and inform micro and small enterprises on issues regarding financing.
Keywords: Financial inclusion; enterprise performance; interest rates capping